The role of TRAF2 in pan-cancer revealed by integrating informatics and experimental validation - Wang, Xizheng; Yuan, Jianfeng; Zhang, Chenchen; Kong, Lingyu; Wu, Enzhen; Guo, Jianxin; Wu, Zhongbing (Frontiers in Pharmacology, 2025)
BackgroundTumor necrosis factor (TNF) receptor associated factor-2 (TRAF2) is an E3 ubiquitin ligase and scaffolding protein that contribute to the progression of various malignant tumors. However, the role of TRAF2 expression in epigenetic, cancer prognosis, and immune responses in tumor microenvironment is unclear.MethodsWe used The Human Protein Atlas (HPA) database, TIMER 2.0 database, and TCGA database to evaluate TRAF2 expression in human normal and tumor tissues. Correlation of TRAF2 expression with mutations and epigenetic in tumors was evaluated using the cBioPortal platform and the GSCA database. To assess the prognostic value of TRAF2, we performed Kaplan-Meier plots and Cox regression analysis. LinkedOmics database was used for PANTHER Pathways enrichment analysis. The relationship between TRAF2 expression and immune checkpoint genes, as well as immune cell infiltration, was examined using TIMER 2.0 and the R language. Single-cell sequencing data and multiple immunofluorescence staining were used to observe the co-expression of TRAF2 on hepatocellular carcinoma cells and immune cells. Furthermore, using siRNA-mediated knockdown, we explored the potential role of TRAF2 in liver cancer cell biology.ResultsOur findings indicate that TRAF2 is frequently mutated and significantly overexpressed in various types of cancers, and this overexpression is linked to a poor prognosis. The epigenetic alterations in TRAF2 was significant across various types of cancers. TRAF2 is associated with the levels of various immune checkpoint genes and multiple tumor-infiltrating immune cells, suggesting its potential involvement in tumor microenvironment. Of note, enrichment analysis revealed a significant correlation between TRAF2 and T cell activation, and single-cell sequencing indicated that TRAF2 was overexpressed in malignant cells and T cells. In vivo results demonstrated that TRAF2 was closely associated with T lymphocytes in hepatocellular carcinoma. The results of our in vitro experimental studies confirmed that the loss of TRAF2 function inhibits the malignant behavior of HepG2 cells in hepatocellular carcinoma.ConclusionTRAF2 represents a potential prognostic biomarker and therapeutic target for cancer immunotherapy, particularly in patients with hepatocellular carcinoma.